2017
DOI: 10.1021/acs.jafc.6b04848
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Rats’ Gut Microbiota Composition in Animals with Different Ginsenosides Metabolizing Activity

Abstract: Following oral intake of Panax ginseng, major ginsenosides are metabolized to deglycosylated ginsenosides by gut microbiota before absorption into the blood. As the composition of gut microbiota varies between individuals, metabolic activities are significantly different. We selected 6 rats with low efficiency metabolism (LEM) and 6 rats with high efficiency metabolism (HEM) from 60 rats following oral administration of Panax ginseng extract, and analyzed their gut microbiota composition using Illumina HiSeq s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…16 Saponins regulate gut microbiota composition and alleviate intestinal inflammatory environment. 28 Here we demonstrated that HFD increased the abundance of Desulfovibrio genus and clostridiales order, and elevated the levels of LPS and DCA in the feces and serums. Conversely, GA modulated gut microbiota and decreased the levels of LPS and DCA in the feces, and thereby prevented pre-metastatic niche formation and metastasis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…16 Saponins regulate gut microbiota composition and alleviate intestinal inflammatory environment. 28 Here we demonstrated that HFD increased the abundance of Desulfovibrio genus and clostridiales order, and elevated the levels of LPS and DCA in the feces and serums. Conversely, GA modulated gut microbiota and decreased the levels of LPS and DCA in the feces, and thereby prevented pre-metastatic niche formation and metastasis.…”
Section: Discussionmentioning
confidence: 60%
“…Saponins, a novel type of plant-derived secondary metabolites, modulate gut microbiota composition and exhibit anti-metastasis activities in multiple tumors including lung adenocarcinoma, hepatocellular carcinoma, and leukemia. 27,28 Glycyrrhizic acid (GA), a triterpenoid saponin glycoside from the licorice roots, inhibits tumor growth and B16 melanoma pulmonary metastasis. 29,30 GA also ameliorates HFD-induced obesity and non-alcoholic fatty liver disease in murine models.…”
Section: Introductionmentioning
confidence: 99%
“…In general, deglycosylation of natural products is regulated by enterobacterial hydrolases. To further elucidate whether differences in the composition of intestinal microbiota result in different activities of hydrolytic enzymes and to analyze the relationships between microbiota enzymatic activity and metabolism, we measured the intestinal microbial glucosidase activities in each group (Dong et al, ). The glycosidase activities in the two model groups were lower than those in the control group, and there was a significant difference between the OACS and ATM groups.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial phylotype richness was estimated by Chao and Ace, and the diversity of the bacterial community was revealed by Shannon [ 17 ]. As shown in Table 1 , there was a significant overall decrease in the richness and the diversity of gut microbiota in the mice fed by HFD ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%